2020
DOI: 10.3389/fcvm.2020.615161
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Integration of Single-Cell Transcriptional Profiling Reveals the Heterogeneities of Non-cardiomyocytes in Healthy and Ischemic Hearts

Abstract: Advances in single-cell RNA sequencing (scRNA-seq) technology have recently shed light on the molecular mechanisms of the spatial and temporal changes of thousands of cells simultaneously under homeostatic and ischemic conditions. The aim of this study is to investigate whether it is possible to integrate multiple similar scRNA-seq datasets for a more comprehensive understanding of diseases. In this study, we integrated three representative scRNA-seq datasets of 27,349 non-cardiomyocytes isolated at 3 and 7 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 49 publications
4
26
0
Order By: Relevance
“…To determine which cell type expressed DCN in the heart, we investigated the level of DCN in our integrated single-cell RNA-sequencing data, which were consisted of fibroblasts, macrophages, neutrophils, endothelial cells, and pericytes ( Zhuang et al, 2020 ). We found that DCN was virtually expressed in fibroblasts ( Supplementary Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…To determine which cell type expressed DCN in the heart, we investigated the level of DCN in our integrated single-cell RNA-sequencing data, which were consisted of fibroblasts, macrophages, neutrophils, endothelial cells, and pericytes ( Zhuang et al, 2020 ). We found that DCN was virtually expressed in fibroblasts ( Supplementary Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…They are the most abundant immune cells in the heart and undergo significant cell flux in injured hearts ( 45 ). Zhuang et al ( 22 ) identified seven macrophage subsets by integrating 27,349 non-myocardial cells after MI and performing single-cell sequencing. Tissue-resident macrophages were selected for the subsequent analyses, and they expressed the repair genes CD163 and Mrc1.…”
Section: Inflammatory Cell Infiltrationmentioning
confidence: 99%
“…Bone marrow-derived, Rel-mediated CD72 hi macrophages play a proinflammatory role in heart injury induction and are, therefore, potential therapeutic targets for various cardiovascular diseases. Zhuang et al found through single-cell sequencing that macrophages from various sources have different transcriptional characteristics, pathways, developmental tracks, and transcriptional regulators ( 22 ). Using single-cell sequencing, Ren et al ( 48 ) found that macrophage activation and subtype conversion are key events in cardiac hypertrophy metaphase.…”
Section: Inflammatory Cell Infiltrationmentioning
confidence: 99%
See 2 more Smart Citations